Multi-parameter quantum metrology - Szczykulska, Magdalena; Baumgratz, Tillmann; Datta, Animesh (Advances in physics: X, 2016)
The simultaneous quantum estimation of multiple parameters can provide a better precision than estimating them individually. This is an effect that is impossible classically. We review the rich background of quantum-limited local estimation theory of multiple parameters that underlies these advances. We discuss some of the main results in the field and its recent progress. We close by highlighting future challenges and open questions.